2008
DOI: 10.12968/bjon.2008.17.3.28409
|View full text |Cite
|
Sign up to set email alerts
|

Exploring knowledge and skills on HIV in student nurses and midwives

Abstract: A cross-sectional survey design using a self-administered questionnaire was sent to a sample of 62 final-year student nurses and midwives to describe their knowledge of, skills related to, and attitudes towards, human immunodeficiency virus/acquired immune deficiency syndrome. Out of the 47 respondents who return the questionnaire, only 53% stated that they had received class instruction on the topic and 63.8% claimed to have increased their knowledge mainly from reading professional journals. Although only 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…This study described university students' knowledge and general attitudes towards HIV and AIDS, as well as their homophobic attitudes and perception of sexual risk behaviour at two Finnish universities. The results showed that although the students' level of knowledge varied, on average they had a good level of knowledge about HIV and AIDS (see also St Rose, 2008;Tung et al, 2008;Veeramah et al, 2008;Nwezeh, 2010). However, there were some students with a very low knowledge level of HIV and AIDS, suggesting that there are still students that need further education about HIV and AIDS issues: accurate HIV and AIDS information is the first step in preventing the spread of this epidemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study described university students' knowledge and general attitudes towards HIV and AIDS, as well as their homophobic attitudes and perception of sexual risk behaviour at two Finnish universities. The results showed that although the students' level of knowledge varied, on average they had a good level of knowledge about HIV and AIDS (see also St Rose, 2008;Tung et al, 2008;Veeramah et al, 2008;Nwezeh, 2010). However, there were some students with a very low knowledge level of HIV and AIDS, suggesting that there are still students that need further education about HIV and AIDS issues: accurate HIV and AIDS information is the first step in preventing the spread of this epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning university students' situation, young adults are at an early stage of sexual behaviour, changing partners frequently, and are therefore at a higher risk of sexually transmitted diseases, including HIV. There are several studies concerning different groups and their knowledge of, and attitudes towards, HIV and AIDS and homosexuality: for instance, people in general (Muinonen et al, 2002;Nkya et al, 2006;Tee & Huang, 2009;Durojaiye, 2009;Samsuddin et al, 2010), students (Huang et al, 2005;Svenson et al 2007;Serlo, 2008;Tung et al 2008;St Rose, 2008;Nwezeh, 2010), and medical and nursing staff (Kermode et al, 2005;Salyer et al, 2008;Umeh et al, 2008;Veeramah et al, 2008). Muinonen with her colleagues (2002) studied HIVrelated knowledge, attitudes and behaviour among a group of young people aged 13-16 years in Finland.…”
Section: Introductionmentioning
confidence: 99%
“…Internationally, nursing students’ knowledge levels regarding HIV and AIDS-related issues have been inconsistent and differences have been noticed in various areas related to HIV and AIDS. Whilst their knowledge level has been reported to be good in European countries such as Finland, the UK, Turkey and Germany [ 7 - 11 ], gaps and weaknesses have also been identified in the same countries (e.g. [ 7 , 10 - 14 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from knowledge level, concerns have been expressed about nursing staff’s negative attitudes and care towards PLWHA [ 19 , 20 ]. Nursing students’ attitudes toward PLWHA have been studied in different countries, and attitudes have varied from rather positive [ 8 , 9 , 11 ], to average [ 7 , 21 ], to negative [ 12 , 13 , 16 , 17 ]. Nursing students have been reported to be apprehensive about caring for PLWHA [ 8 , 22 ] and associations between background factors and attitudes have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that nursing students with negative attitudes toward PLWAs were less willing to care for patients with HIV/AIDS when compared to students with more positive attitudes (Lohrmann et al 2000, Cornelius 2004). Veeramah et al (2008) found that, among nursing students, higher HIV/AIDS knowledge levels were associated with more positive attitudes. Studies have also demonstrated improvement in student nurses' knowledge and attitudes about HIV/AIDS and increased compliance with universal precautions after educational interventions (Uwakwe 2000, Pisal et al 2007.…”
Section: Introductionmentioning
confidence: 93%